I need the solution to the problem: log2 ((x^2)+1)-log4 (x^2) = 1 It gives me a hint to change log4 (x^2) to base 2, but I'm not sure how to go about doing that.
Follow Math Help Forum on Facebook and Google+
Originally Posted by ceasar_19134 I need the solution to the problem: log2 ((x^2)+1)-log4 (x^2) = 1 It gives me a hint to change log4 (x^2) to base 2, but I'm not sure how to go about doing that. A clearer hint: $\displaystyle \log_4 {x} = \frac{\log x}{\log 4} = \frac{\log x}{2\log 2} = \frac{\log_2{x}}{2}$ Now you can rewrite everything in terms of $\displaystyle log_2$. Complete it
View Tag Cloud